(untitled) (Experimental biology, 2023)
The study of biodiversity in key areas and conservation corridors in the Central Asian mountainous region is becoming increasingly relevant in light of large-scale anthropogenic interventions in the natural environment. Particularly hydropower development leads to habitat alteration and fragmentation, reducing the biodiversity of aquatic organisms. At the same time, science does not have sufficient information about the biogeography of large aquatic organisms such as fish in mountain rivers of Central Asia. This study presents fish ecological data from field surveys conducted in 2021–2022 at Koksu River, Shakhimardan river basin, Uzbekistan. Contrary to statements about the absence of fish from Koksu River, we confirm the presence of two fish species: snow trout (Schizothorax eurystomus Kessler, 1872) and stone loach (Triplophysa ferganaensis Sheraliev and Peng, 2021). Further studies should assess habitat preferences and migration patterns of the discovered fish to support conservation and restoration frameworks.